Genomic profiles and clinical outcomes of de novo blastoid/pleomorphic MCL are distinct from those of transformed MCL - Jain, Preetesh (Blood Adv, 2020)
Blastoid and pleomorphic mantle cell lymphomas (MCLs) are variants of aggressive histology MCL (AH-MCL). AH-MCL can arise de novo (AH-DN) or transform from prior classic variant MCL (AH-t). This study is the first integrated analysis of clinical and genomic characteristics of AH-MCL. Patient characteristics were collected from diagnosis (AH-DN) and at transformation (AH-t). Survival after initial diagnosis (AH-DN) and after transformation (AH-t) was calculated. Regression tree analysis was performed to evaluate prognostic variables and in univariate and multivariate analyses for survival. Whole-exome sequencing was performed in evaluable biopsy specimens. We identified 183 patients with AH-MCL (108 were AH-DN, and 75 were AH-t; 152 were blastoid, and 31 were pleomorphic). Median survival was 33 months (48 and 14 months for AH-DN and AH-t, respectively; P = .001). Factors associated with inferior survival were age (≥72 years), AH-t category, Ki-67 ≥50% and poor performance status. AH-t had a significantly higher degree of aneuploidy compared with AH-DN. Transformed MCL patients exhibited KMT2B mutations. AH-MCL patients with Ki-67 ≥50% had exclusive mutations in CCND1, NOTCH1, TP53, SPEN, SMARCA4, RANBP2, KMT2C, NOTCH2, NOTCH3, and NSD2 compared with low Ki-67 (<50%). AH-t patients have poor outcomes and distinct genomic profile. This is the first study to report that AH-MCL patients with high Ki-67 (≥50%) exhibit a distinct mutation profile and very poor survival.